Endocrine regulation of adipose tissue thermogenesis in the fetal and neonatal sheep - Mostyn, Alison (2001)
Leptin is produced primarily by white adipose tissue but also by brown adipose tissue (BAT) and the placenta. It has a major physiological role in the control of energy balance. BAT is critically important for the initiation of non-shivering thermogenesis in precocial newborns through the uncoupling protein, UCP1 unique to BAT. This is particularly important in neonatal lambs and infants in which levels of UCP1 peak at birth concomitant with a peak in plasma leptin and a surge in Cortisol. Other mitochondrial proteins may contribute to this effect e.g. VDAC which is located in the outer mitochondrial membrane. The aim of this thesis was to: